Validation of the Casa Colina Fall Risk Assessment Scale in Predicting Falls in Inpatient Rehabilitation Facilities. Issue 4 (July 2020) - Kaplan, Stephanie E.; Cournan, Michele; Gates, Jason; Thorne, Melanie; Jones, Annette; Ponce, Tom; Rosario, Emily R.
Abstract: Objective: The aim of this study was to assess the validity, efficacy, and generalizability of a fall risk assessment tool created specifically for inpatient rehabilitation facilities (IRFs). Design: The Casa Colina Falls Risk Assessment Scale (CCFRAS) was assessed both retrospectively and prospectively on consecutive patients at three IRFs to determine the sensitivity and specificity of this tool in predicting fall risk. Setting: The setting was in three IRFs. Participants: Individuals admitted to three IRFs participated in the study. Main Outcomes Measures: Each IRF quantified the number of falls detected for the patient population under evaluation and determined the site-specific sensitivity and specificity of the CCFRAS. Results: The sensitivity and specificity of the CCFRAS ranged from 75% to 80% and from 47% to 70%, respectively, for the different IRFs. Using a logistic regression analysis, we identified the optimal CCFRAS cutoff score for identifying high-risk patients at each individual facility, thus improving the specificity to 70%–79%. Conclusion: Multisite evaluation of this assessment tool indicates that the CCFRAS is effective and broadly generalizable for predicting patients at high risk for falling.